(untitled) (Journal of the College of Basic Education, 2023)
The quality of life for some is represented by the possession of wealth that brings them happiness. while some see it The other is in the life in which there are opportunities to work and study, and others see it in the life in which the individual is ableFrom getting what he wants without trouble or effort, and others define it as a life free from fraud and deceptionLying, or others may define it as a life full of physical and psychological health free from diseaseand disturbances. Whatever the meaning of the concepts. And how the individual defines the quality of life has lost a goalcurrent search measure: 1. Doing good for university students improves quality of life? 2. Significant differences between university students in the sense of quality of life according to the variables of sex And academic major?